Stimulating urban renewal; through forging connection between architecture + public infrastructure towards an integral urbanism - Truter, Clive Warren (School of Architecture, Planning and Geomatics, 2016)
In this dissertation I discuss the significance of field conditions to offer architecture a strategic dimension to evaluate process and enable public infrastructure with the potential to become catalytic towards an integral urbanism. Inscribed in this idea is a recognition that conventional architectural and planning practices are deficient to anticipate new alternatives in isolation; is that these traditional approaches are unsuccessful in negotiating mass mobility, interrelationships and perceptions in the contemporary city. Objectives The first objective is to transcend beyond traditional perceptions of infrastructure and develop an understanding of what infrastructure could be, through reconfiguring how it functions holistically in the urban landscape. Secondly, the aim is to formulate a comprehension of field conditions, through siting its significance for architecture as a strategic process-driven medium, to decode [or notate] latent and progressive urban scenarios. The third objective is located in the proposition, which explicitly notates a shift from the conventional notion of urban renewal, as we have come to understand it locally towards an integral urbanism. This aim of this is to investigate